Exploring water usage practices of kitchen staff in restaurants in the Vaal Region - Van der Merwe, Etresia (Vaal University of Technology, 2019)
The tourism and hospitality industry uses vast amounts of water during general household activities and food service, food preparation, cooking, cleaning, and other kitchen duties. In addition, over the past years, water usage has increased due to the growth in the population, technology, lifestyle changes, and the increasing demand of the tourism and hospitality industry. It is evident that the demand for clean fresh water is growing immensely and saving water by all organisations can contribute to conserving water for future use. This study involves exploring water usage management practices of kitchen staff in restaurants in the Vaal region. Therefore, the research question was, what are the employee habits and/or practices regarding wasting as well as saving water in restaurants? A qualitative observational design was used during this research study. Ethical clearance was obtained from the Vaal University of Technology before fieldwork commenced. After identifying 53 restaurants within the Vaal region (Vanderbijlpark, Vereeniging, and Sasolburg), convenience sampling was used to select the restaurants for observations. Nineteen owners and supervisors gave consent, whereupon the restaurant kitchen staff were observed to determine their water usage practices and habits. Staff was not made aware of what was being observed and this created a more naturalistic environment. Information gathered from the observations was done until data saturation had been reached. The data collected was captured and coded making use of Atlas Tl programme in order to identify concepts, categories, and themes. Form the results, six themes were identified. The majority of water wastage occurred during water disposal. Other water usage and wastage occurred during rinsing and tap use, with incorrect tap use, such as leaving the tap running and not properly closing the tap. Although various water practices and habits were observed within many restaurants, some water saving practices and habits also played a role in kitchen activities. Water saving was mainly done through the habits and practices of cleaning procedures, such as the removal of debris by scraping off scraps of food or softening debris before dishwashing. Other saving habits and procedures included using water readily available during cleaning. During the process of observation and fieldwork, it was noticed that very few posters on correct handwashing procedures or correct water and equipment usage were displayed in participating restaurants. This phenomenon raised the question of whether the lack of communication of water usage, hand washing, and equipment usage was a contributing factor to water wastage occurring frequently. Therefore, the recommendations for future studies include the testing of staff knowledge and the impact of implementing communication tools, for instance, posters in restaurants on sustainable water usage. Consideration also needs to be made to assess if water saving policies and procedures are in place and being practiced. Further attention should also be given t training and education of staff on water usage, which could raise awareness on water sustainability. Considering that water usage and especially wastage is present in restaurants, future studies may also focus on the amount of water wastage that occurs within these organisations.
M. Tech. (Department of Hospitality, Tourism and PR Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Restaurants; Water usage practices; Water usage habits; Water usage awareness; Water saving; Water wastage; Dissertations, Academic -- South Africa.; Restaurants -- Waste disposal.; Water use.; Water-supply -- Management.